Promotion of physical activity for adolescents with cystic fibrosis: A qualitative study of UK multi-disciplinary cystic fibrosis teams - Melitta McNarry (Physiotherapy, 2019)
BackgroundThe Cystic Fibrosis Trust recently published a standards of care document which stated that patients should be given a physical activity (PA) programme based on their motivations, fitness, and willingness to be active. However, there remains much debate regarding the roles and responsibilities for PA promotion, as well as “optimal” recommendations and advice. This study aimed to qualitatively explore cystic fibrosis (CF) multidisciplinary teams (MDTs) advice, recommendations and practices relating to PA promotion for adolescents with CF.MethodSemi-structured interviews were conducted with fifteen members of CF MDTs (11 physiotherapists, two dieticians and two paediatricians). Thematic analysis was used to analyse the data.ResultsMajor themes identified were: 1) structure of MDTs, 2) recommendations relating to intensities, durations and types of PA, and 3) use of exercise testing. Participants reported variation between MDTs in terms of who is responsible for promoting and supporting PA, the nature of advice given to patients, and the use of exercise testing. Participants consistently lacked confidence in their own or others’ knowledge to provide standardised recommendations to patients and highlighted that PA promotion and support was often overlooked during busy periods.ConclusionsDespite its importance, PA support and promotion is not always prioritised. MDTs lack confidence in their ability to promote PA. Standardised advice and training relating to optimal intensities, durations and types of PA would provide a baseline from which to individualise advice to each patient and could increase confidence in PA promotion among MDTs.